1998
DOI: 10.1103/physrevb.57.8823
|View full text |Cite|
|
Sign up to set email alerts
|

Formation of a bilayer ordered surface alloy Mn/Ag(001)

Abstract: Low-energy electron diffraction I/V analyses reveal that Mn thin films deposited on Ag͑001͒ at room temperature form substitutional, ordered, bilayer Mn 50 Ag 50 surface alloys. The Mn atoms in this structure have local magnetic moments of considerable value, as judged from the Mn 3s core level spectra; these local magnetic moments of Mn are effective in the formation of the ordered surface alloy. Ab initio total energy calculations have been done and the results confirmed the experimental observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Meanwhile, a significant number of additional c(2ϫ2) MnX/X surface alloys have been found, i.e., XϭCu(110), 13 Co͑100͒, 14 Ni͑100͒, 15 Pd͑100͒, 16 and Ag͑100͒. [17][18][19] A recent set of scanning tunneling microscopy ͑STM͒ studies [20][21][22] confirmed the existence of a c(2ϫ2) surface unit cell, although only one chemical component of the surface alloy was imaged ͑for a typical STM image, see Fig. 5͒.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, a significant number of additional c(2ϫ2) MnX/X surface alloys have been found, i.e., XϭCu(110), 13 Co͑100͒, 14 Ni͑100͒, 15 Pd͑100͒, 16 and Ag͑100͒. [17][18][19] A recent set of scanning tunneling microscopy ͑STM͒ studies [20][21][22] confirmed the existence of a c(2ϫ2) surface unit cell, although only one chemical component of the surface alloy was imaged ͑for a typical STM image, see Fig. 5͒.…”
Section: Introductionmentioning
confidence: 98%
“…In order to compare the stability of the substitutional adsorption with that of the on-surface adsorption it is necessary to define the adsorption energy per adatom. For on-surface adsorption, the adsorption energy per adatom is defined as [15] E ad = (E Mn/Ni−slab − E Ni−slab − nE Mn−atom )/n, (1) where E Ni−slab and E Mn/Ni−slab are the total energies of a clean Ni surface and the adsorbate system, respectively, n is the number of Mn atoms and E Mn−atom is the total energy of a spin-polarized free Mn atom. In the case of Mn substitutional adsorption, a substrate atom is kicked out and moves to a kink site at a surface step, while an adsorbate atom moves to occupy the vacancy.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…An extensive experimental study of Fe and Ni(001) surfaces and the overlayer system (Ni/Fe) show some of the structural changes which depend on the number of Ni layers grown on Fe substrate [5,6]. While previous theoretical studies are restricted to one-and two-pure Ni overlayers on Fe(001), the inter-mixing of Ni-Fe at the interface is confirmed by experiments.The effects of magnetism on stability and alloy formation of the overlayer were under experimental and theoretical investigations [7][8][9][10][11]. These studies have included non-magnetic (Ag, Cu) overlayers on a magnetic (Fe) substrate.…”
mentioning
confidence: 99%
“…In order to identify the equilibrium configuration of Ni overlayer on Fe substrate; we have examined the formation energy gain by altering the order, the number of Ni atoms, and the number of Ni layers. The stability of the surface alloy formation is examined using a convention of energy calculation reported elsewhere [7,8]. …”
mentioning
confidence: 99%